2010
DOI: 10.1007/s10562-010-0304-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Oxygen Reduction Reaction and Oxidative Dehydrogenation Activities Over Nanostructured Carbon Catalysts

Abstract: Nitrogen containing nano-structured carbon catalysts were grown on Fe/Al 2 O 3 and Ni/Al 2 O 3 supports using acetonitrile pyrolysis. The post-pyrolysis samples were tested for activity in the oxygen reduction reaction (ORR) and oxidative dehydrogenation (ODH) reaction. Samples were characterized using BET, XPS and TEM. The samples grown over iron containing supports gave the highest activity in both reactions. There was a strong correlation between ODH and ORR activity suggesting the possibility of a common a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 43 publications
0
26
1
Order By: Relevance
“…ysis of the cyclic voltammograms, part of these defects consist of quinone groups on the surface, that in previous studies were found to improve ORR or even to be the active catalyst for it [31]. However, the quantity of defects found is lower than for example in Vulcan XC72 (0.94) which we analyzed as a representative of commercial support since for the one used in HISPEC 9100, named Carbon ACO1 by the supplier, no data were available.…”
Section: Original Research Papermentioning
confidence: 90%
“…ysis of the cyclic voltammograms, part of these defects consist of quinone groups on the surface, that in previous studies were found to improve ORR or even to be the active catalyst for it [31]. However, the quantity of defects found is lower than for example in Vulcan XC72 (0.94) which we analyzed as a representative of commercial support since for the one used in HISPEC 9100, named Carbon ACO1 by the supplier, no data were available.…”
Section: Original Research Papermentioning
confidence: 90%
“…[534]. Similarly, NCNFs containing a range of nitrogen contents of 1−10 atom % were directly synthesized by catalytic CVD over nickelbased catalysts at 350−600 °C using CH 3 CN and acrylonitrile as a CN x source [535].…”
Section: Preparation Of Ncnhs and Their Compositesmentioning
confidence: 99%
“…Similarly, the N 1s spectrum revealed the presence of pyridine-type N (398.5 eV), N(1), and pyrrole-/pyridone-type N (400.5 eV), N(2) (Scheme 2) [17][18][19][20]. Table 1 however, such trend was not significant for the N-doping with NO.…”
Section: Resultsmentioning
confidence: 93%
“…Typical XPS spectra in the O 1s and N 1s regions are depicted in Figure 1. The O 1s spectrum could be deconvolved into two peaks at 531.8 and 533.3 eV attributed to O species of C=O, O(1), and of C-O-C, O(2), respectively [16,17].…”
Section: Resultsmentioning
confidence: 99%